PENERAPAN STRATEGI PEMASARAN MELALUI MEDIA SOSIAL WHATSAPP BUSINESS UNTUK MENINGKATKAN PENJUALAN PADA FIT.ME HIJAB - Bima Yunus Dzulhanto; Fitri Khotijah; Inenimas Arya Renjani; Yusuf Ramadhan; Pramono Pramono (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The advancement of information technology has transformed the global marketing landscape, driving businesses to shift from conventional methods to digital strategies. This study aims to analyze the implementation of marketing strategies through the social media platform WhatsApp Business to increase sales at Fit.Me Hijab. Utilizing a qualitative research method, data was collected through interviews, observations, and documentation to evaluate the effectiveness of WhatsApp Business features in supporting marketing activities. The research findings indicate that the use of WhatsApp Business, particularly the product catalog, broadcast messages, and automated responses features, significantly enhances customer interaction and product sales. Prior to using WhatsApp Business, Fit.Me Hijab's sales were around 10 products per month; after adopting the platform, sales increased to 30 products in November and 46 products in December. These findings suggest that WhatsApp Business is an effective marketing tool for SMEs, enabling more personal and efficient interactions with customers. This study provides practical insights for business practitioners to optimize the use of social media as part of their digital marketing strategy.